Personal style of the therapist and personality dimensions in a sample of Argentinian therapists - Casari, Leandro Martín (2019)
Fil: Casari, Leandro Martín. Pontificia Universidad Católica Argentina. Facultad de Humanidades y Ciencias Económicas; Argentina